A systematic review of the health of internal migrants in Bangladesh. (12th November 2021) - Akhter, Sadika; Mahmood, Nabila; Rutherford, Shannon
Abstract: Internal migrants are more disadvantaged than non‐migrants in terms of their health. However, the extent of this difference is unclear. Following the PRISMA guideline, we conducted a systematic review to explore the existing evidence on the health of internal migrants of Bangladesh. We searched Pubmed, Web of Science and Google Scholar to identify peer‐reviewed literature on health related issues of the internal migrant population and identified 29 papers for inclusion. Included studies reported health issues or risk factors relating to water, sanitisation and hygiene access and practice, risky sexual behaviour and sexually transmitted infection, mental health status, occupational health status, general healthcare availability, healthcare service utilisation and healthcare seeking behaviour. This systematic review reveals that research on health issues of internal migrants of Bangladesh is limited for common communicable and noncommunicable diseases like waterborne and skin disease, tuberculosis, hypertension and diabetes. Further, despite that many of these migrants are labourers, occupational health related issues like work place accidents, musculoskeletal disorders are insufficiently explored. Barriers to healthcare accessibility in this population are poor socioeconomic status, illiteracy and low general health knowledge. For improved development and implementation of health policies targeting this important population, future studies should focus on understudied diseases and disease prevalence and be designed to elicit from the perspectives of internal migrants, their key health needs around risk factors and health services accessibility. Highlights: Internal migrants are more disadvantaged than non‐migrants in terms of their health. However, it is still not clear how severe the problem is This systematic review reveals that research on health issues of internal migrants of Bangladesh is limited for common communicable and non‐communicable diseases like waterborne and skin disease, tuberculosis, hypertension and diabetes Despite that many of these internal migrants are labourers and their occupational health‐related issues like work place accidents, musculoskeletal disorders are insufficiently explored These internal migrants face challenge to access healthcare due to their poverty and low knowledge on general health Future studies should focus on understudied disease types and diverse methods to not only understand prevalence but also qualitative information on health needs, priorities and other health service access barriers